Impact resistance of self-sensing engineered cementitious composite (ECC) under different temperatures - Jinsheng Han; Xinyu Shi; Jinlong Pan; Zhigang Song; Peng Wang; Jingming Cai; Guohui Zhang (Case Studies in Construction Materials)
Self-sensing engineered cementitious composite (ECC) is inevitably susceptible to the effects of impact loads when it is applied to structural health monitoring. In this paper, the impact resistance of self-sensing ECC under varying temperatures was investigated by experiments. Specimens comprising cement mortar, conventional ECC, and self-sensing ECC, all featuring identical water-binder ratios, were prepared and subjected to compressive and tensile strength evaluations, as well as tensile ductility measurements. Subsequently, the drop-weight impact tests were conducted on these three specimens at the temperatures of −50℃, −30℃, −10℃, 20℃, 50℃ and 100℃, respectively. Detailed analyses were carried out on the resulting impact loads, impact durations, dent depths, and failure modes. Our findings reveal that the compressive strength of cement mortar surpasses that of both conventional ECC and self-sensing ECC. Furthermore, conventional ECC and self-sensing ECC exhibit ultimate tensile strains of 4.6 % and 6.7 %, respectively. At the same drop-height of impactor, the maximum impact force decreases with the increase of temperature. At cold temperature, the specimen exhibit heightened impact forces coupled with abbreviated impact durations. Self-sensing ECC demonstrates a decreased maximum impact force and an extended duration compared to conventional ECC. The cement mortar specimen shows brittle failure, while both self-sensing ECC and conventional ECC align with the scabbing failure mode. Self-sensing ECC with a smaller scabbing thickness has preferable impact resistance and deformability.